A Prospective Observational Study on Prevalence of Anemia, Associated Risk Factors and Outcome - Phocas Havugimana; Raphael Ndahimana; Felix Babane; Ernestine Umutesi; Polyphile Ntihinyurwa; Diane Mushimiyimana; Florence Masaisa; Etienne Ntabanganyimana (Ital Publication, 2022)
Background: Admitted patients with anemia are at increased morbidity and mortality risk, as well as length of hospital stay. It affects more than 2 billion people worldwide and is causing significant morbidity and mortality. Its etiology is variable, with many predisposing factors including nutritional deficiencies, infections, malignancies, chronic inflammations, and other chronic diseases like autoimmune diseases, chronic liver disease, and chronic kidney disease. Methods: We performed a non-randomized, prospective observational study of 143 patients admitted to internal medicine between March and April 2021 and assessed their hemoglobin level in order to determine the prevalence of anemia. The demographic and clinical data were collected using a specially designed questionnaire. All patients found to have anemia were followed for outcome assessment (either discharge or death). Results: The prevalence of anemia was high (52.4%) among the 143 admitted patients in internal medicine at CHUK. Patients with HIV, cancer, and chronic kidney disease had a 5.84-, 4.11-, and 3.79-times higher risk of having anemia, respectively. In 75 patients who had anemia, 10 patients died; among them, 5 patients had severe anemia; 25 patients were 60 years old and above; 60 patients had normocytic anemia, and they had an average length of hospital stay of 20.6 days; for patients with severe anemia, the length of hospital stay was 28 days. Conclusion: This study demonstrated a high prevalence of anemia, which is associated with a high mortality rate among admitted patients in CHUK. Priority should be given to preventive medicine, optimal management of chronic disease, and geriatric medicine.   Doi: 10.28991/SciMedJ-2022-04-02-05 Full Text: PDF